2020
DOI: 10.1371/journal.pone.0241513
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical and X-ray structural studies of the (GGGTT)3GGG G-quadruplex in complex with N-methyl mesoporphyrin IX

Abstract: The G-quadruplex (GQ) is a well-studied non-canonical DNA structure formed by G-rich sequences found at telomeres and gene promoters. Biological studies suggest that GQs may play roles in regulating gene expression, DNA replication, and DNA repair. Small molecule ligands were shown to alter GQ structure and stability and thereby serve as novel therapies, particularly against cancer. In this work, we investigate the interaction of a G-rich sequence, 5’-GGGTTGGGTTGGGTTGGG-3’ (T1), with a water-soluble porphyrin,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 53 publications
2
18
1
Order By: Relevance
“…The earliest reported crystal structures of G4/ligand complexes were the tetramolecular G4/daunomycin complex [ 164 ] and the telomeric G4 from Oxytricha nova/acridine derivative complex [ 165 ]. Since then, several G4/ligand complexes have been characterized using X-ray crystallography [ 166 , 167 , 168 , 169 ].…”
Section: Methods To Characterize G4/ligand Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The earliest reported crystal structures of G4/ligand complexes were the tetramolecular G4/daunomycin complex [ 164 ] and the telomeric G4 from Oxytricha nova/acridine derivative complex [ 165 ]. Since then, several G4/ligand complexes have been characterized using X-ray crystallography [ 166 , 167 , 168 , 169 ].…”
Section: Methods To Characterize G4/ligand Interactionsmentioning
confidence: 99%
“…Lin et al investigated the interaction of the G4 forming sequence, 5′-GGGTTGGGTTGGGTTGGG-3′ (T1) and several other sequences based on T1, with the G4 ligand, N-methyl mesoporphyrin IX (NMM) by biophysical and X-ray crystallographic studies [ 166 ]. They solved the crystal structure of T1- and 5′-TGGGTTGGGTTGGGTTGGGT-3′ (T7)-NMM complexes.…”
Section: Methods To Characterize G4/ligand Interactionsmentioning
confidence: 99%
“…An earlier study of TET22 in 100 mM KCl reported its stability to be >80°C ( 12 ), consistent with our value of 76.4°C in 10K buffer when the effect of potassium on GQ stability is considered. Specifically, in our earlier work we demonstrated that the stability of another G-rich sequence, T1 , increased from 65.6°C in 20 mM K + buffer to 76.7°C in 100 mM K + buffer ( 23 ). The fact that T 1/2 is similar (within 5°C) for all four G-tetrad TET GQs agrees with the recent finding by Mergny and Li laboratories who discovered no correlation between conformation and stability for 99 three G-tetrad GQs ( 38 ).…”
Section: Resultsmentioning
confidence: 89%
“… **Poorly defined melting transition. % data from ref ( 23 ) for T1 and T7 and from ref ( 24 ) for 19wt in 5K buffer (5 mM KCl, 95 mM LiCl and 10 mM lithium cacodylate 7.2). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation